Nickel Loaded into Three-Dimensional Porous Composite Materials Doped by Nitrogen Atoms for Accelerating the Conversion Process of Polysulfides - Lu, Jixin; Zhu, Mengyuan; Wang, Lukuan; Cui, Yangyang; Wu, Chunjie; Bi, Qiaoling; Jiang, Shaoyu; Zhao, Qing; Zhao, Jianxin; Liu, Linjing; Wang, Cunguo; He, Aihua (Journal of Composites and Biodegradable Polymers, 2025)
The industrial deployment of lithium–sulfur batteries remains hindered by sulfur’s intrinsically low electrical conductivity and the pronounced shuttle effect that arises during cycling. In this study, a novel porous composite material (GA/Ni-CN) was prepared by loading the nickel metal catalyst onto nitrogen-doped three-dimensional graphene aerogel carbon-based materials. Graphene aerogel and ZIF-derived nitrogen-doped carbon framework composites provide abundant polar sites while maintaining a stable three-dimensional porous structure, enhancing polysulfide adsorption. A small amount of metallic nickel phase serves as the electrocatalytic center, accelerating the redox conversion of polysulfides while preventing catalyst overconsumption. The battery assembled with S@GA/Ni-CN as the cathode material exhibits excellent electrochemical performance and shows high electrochemistry response in cyclic voltammetry testing. In addition, the initial discharge specific capacity got to 1482 mAh/g at 0.2 C current density, substantially surpassing the sulfur utilization efficiency of conventional carbon-based materials.